An Indigenous Research Methodology That Employs Anishinaabek Elders, Language Speakers and Women’s Knowledge for Sustainable Water Governance - Susan Chiblow (Water, 2020)
Indigenous research paradigms are congruent to Indigenous worldviews and have become more dominant in areas such as Indigenous policy and education. As Indigenous research paradigms continue to gain momentum, the historical legacy of unethical research is addressed as more Indigenous communities and organizations develop their own research protocols. There is a plethora of articles explaining Indigenous research methodologies, but few examine the inclusion of the knowledge from Elders, language speakers, and Indigenous women in sustainable water governance. My Indigenous research methodology draws on the works of Indigenous scholars Shawn Wilson, Linda Smith, and Margaret Kovach, with specific focus on Wendy Geniusz’s Biskaabiiyang. My Indigenous research methodology is specific to the Anishinaabe territory of the Great Lakes region and includes Anishinaabek Elders, Anishinaabemowin (Ojibway language) speakers, and Anishinaabek women. This article seeks to contribute to Indigenous research paradigms and methods by elucidating the importance of engaging Anishinaabek Elders, Anishinaabemowin speakers, and Anishinaabek women in sustainable water governance.